Long-Term Mating Orientation in Men: The Role of Socioeconomic Status, Protection Skills, and Parenthood Disposition - Fajardo, Gabriela; Polo, Pablo; Muñoz-Reyes, José Antonio; Rodríguez-Sickert, Carlos (Frontiers in Psychology, 2022)
From an evolutionary perspective, phenotypic, social, and environmental factors help to shape the different costs and benefits of pursuing different reproductive strategies (or a mixture of them) from one individual to another. Since men’s reproductive success is mainly constrained to women’s availability, their mating orientations should be partially calibrated by features that women prefer in a potential partner. For long-term relationships, women prefer traits that signal access to resources, protection skills, and the willingness to share them. Using generalized linear models with laboratory data taken from a Chilean population (N = 197), this study aimed to test whether real and potential resources (measured as self-reported socioeconomic status), protection skills (measured as handgrip strength), and the willingness to provide resources and protection (measured as their disposition towards parenthood) are related to mating orientation in men. Our predictions were: (1) socioeconomic status would be positively associated with long-term and short-term mating orientation but for long-term-oriented individuals, this would be enhanced by having a more favorable parenthood disposition and (2) strength would be positively related to long-term mating orientation in men with higher socioeconomic status and a favorable disposition towards parenthood and it would have a positive and direct association with short-term mating orientation. Our results partially supported the first hypothesis, since men with higher socioeconomic status were more long-term oriented, but parenting disposition did not moderate this effect. Contrary to our expectations, socioeconomic status was not related to short-term mating orientation. Strength appeared not to be significant for long-term mating orientation, even interacting with other traits. However, strength by itself was powerfully linked with a short-term mating orientation. Our results suggest that only some individuals that are attractive for long-term relationships are indeed long-term oriented and may reflect the overall conflict of interests between mating strategies among sexes.